Sensing TFT Vth by an external algorithm to compensate non-uniformity on AMOLED panel - Kuei-Yu Lee; Chao, Paul C.-P (2012 IEEE Sensors, 2012)
The study proposes an external algorithm to compensate non-uniformity on AMOLED panel. With the method of sensing TFT V th variation, this external algorithm is designed to correct the data line voltage, V data , in order to maintain the required OLED luminance even though every V th variation of driving TFTs are different. The algorithm and sensing method are realized on the already proposed 4T0.5C pixel circuit, which is investigated to show the performance of panel non-uniformity compensation in the experiment results. Moreover, the original merits of 4T0.5C pixel circuit like OLED degradation alleviation can be maintained.